2006
DOI: 10.1080/09553000600876678
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude and time-dependence of the apoptotic response of normal and malignant cells subjected to ionizing radiation versus hyperthermia

Abstract: These studies reveal time and temperature dependent in vitro cell responses to ionizing radiation and water-bath hyperthermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…Cells in 8-chamber Labteks were treated in parallel, and at 24 h the cell free ECM in labteks was fixed with methanol, rinsed with PBS, blocked with normal serum for 30 min and then visualized using indirect immunohistochemistry with rabbit IgG raised to human fibronectin (Zymed Laboratories, San Franciso, CA) visualized using FITC-labeled anti-rabbit antibody conjugates (1:100). The cellfree ECMs were also stained after methanol fixation using 4′6-diamidino-2-phenlindole to detect DNA, as described previously by us (Vorotnikova et al, 2006). The unfixed flask derived cell-free matrix and the cell preparations derived from MRL-B cultures in the T-150 flasks, were normalized for cell numbers and either incubated in a mammalian cell lysis and extraction RIPA buffer consisting of 25 mM Tris-HCl pH 7.6, 150 mM NaCl, 1% NP-40, 1% Sodium deoxycholate and 0.1% SDS from Pierce Products (Thermo Fisher Scientific, Rockford, IL.)…”
Section: Mrl Blastemal Cell Matrix Isolationmentioning
confidence: 99%
“…Cells in 8-chamber Labteks were treated in parallel, and at 24 h the cell free ECM in labteks was fixed with methanol, rinsed with PBS, blocked with normal serum for 30 min and then visualized using indirect immunohistochemistry with rabbit IgG raised to human fibronectin (Zymed Laboratories, San Franciso, CA) visualized using FITC-labeled anti-rabbit antibody conjugates (1:100). The cellfree ECMs were also stained after methanol fixation using 4′6-diamidino-2-phenlindole to detect DNA, as described previously by us (Vorotnikova et al, 2006). The unfixed flask derived cell-free matrix and the cell preparations derived from MRL-B cultures in the T-150 flasks, were normalized for cell numbers and either incubated in a mammalian cell lysis and extraction RIPA buffer consisting of 25 mM Tris-HCl pH 7.6, 150 mM NaCl, 1% NP-40, 1% Sodium deoxycholate and 0.1% SDS from Pierce Products (Thermo Fisher Scientific, Rockford, IL.)…”
Section: Mrl Blastemal Cell Matrix Isolationmentioning
confidence: 99%
“…Images were obtained using fluorescence microscopy (Olympus, Center Valley, PA). Mitotic, apoptotic and interphase DNA morphology could be seen by DAPI as previously reported by us [24,25]. The DAPI images were taken using an excitation wavelength filter of 350 nm and the Lava Cell images were taken using an excitation wavelength filter of 534 nm.…”
Section: Methodsmentioning
confidence: 68%
“…It has been utilized in stereotactic radiotherapy for the treatment of intracranial or body trunk tumors [1], but little is known concerning histological changes after such high-dose irradiation. Laboratory studies have suggested that cell death after high-dose irradiation occurs mainly by apoptosis rather than necrosis [2][3][4]. After irradiating human promyelocytic leukemia cells with 10 or 50 Gy of X rays, Dynlacht et al studied the cells for up to 72 h. After 50 Gy irradiation, cells were found to die primarily by apoptosis, while cells irradiated with 10 Gy died predominantly by necrosis [2].…”
Section: Introductionmentioning
confidence: 97%
“…After irradiating human promyelocytic leukemia cells with 10 or 50 Gy of X rays, Dynlacht et al studied the cells for up to 72 h. After 50 Gy irradiation, cells were found to die primarily by apoptosis, while cells irradiated with 10 Gy died predominantly by necrosis [2]. Human colorectal carcinoma cells irradiated with 20 Gy by Vorotnikova et al [3] showed apoptosis but not necrosis. However, in vivo studies which investigated histological changes after radiation therapy have failed to offer enough evidence that high-dose irradiation causes apoptosis rather than necrosis [5][6][7].…”
Section: Introductionmentioning
confidence: 97%